Digital Society’s and Social Solidarity: A Study on the Philanthropic Institution Dompet Dhuafa in Building Humanitarian Connectivity - Sidiq, Rd. Siti Sofro; Armilus, Robi; Dzulqarnain, Muhammad Faizal; Sugiyanto, Seger; Mohamed, Sheik (LITPAM, 2026)
This study aims to analyze and understand the development of solidarity in a continuously changing society, especially in the digital era. The unit of analysis in this study is the Dompet Dhuafa platform, a prominent humanitarian organization in Indonesia that focuses primarily on social welfare and community empowerment. The research method employed is a document study using publicly available publications from the Dompet Dhuafa website. This study finds that Dompet Dhuafa is a popular platform for facilitating the fulfillment of religious obligations, particularly for Muslims, such as zakat and infaq. However, this platform is also open to all segments of society. These findings show that Dompet Dhuafa plays an important role in connecting various layers of society through digital donation channels, which make it easier for the public to participate in social activities without the limitations of distance and time. The study also provides recommendations regarding the importance of strengthening data protection and transaction policies during the donation process to prevent cybercrimes by irresponsible parties. Furthermore, the study suggests further research on the contributions of various virtual donation platforms to social welfare across different sectors. This is crucial to strengthen the role of virtual solidarity in empowerment and social welfare and to create a broader impact in advancing collective good.